2014
DOI: 10.1016/j.tourman.2013.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Job involvement, commitment, satisfaction and turnover: Evidence from hotel employees in Cyprus

Abstract: h i g h l i g h t sWe investigate job satisfaction, involvement, organizational commitment and turnover intentions. Affective and normative organizational commitment, have positive associations with job satisfaction. Affective organizational commitment and satisfaction have negative associations with turnover. A negative association between intrinsic job satisfaction and turnover intention cannot be supported. a r t i c l e i n f o t r a c tThe study of attitudes at work seeks to enhance organizational knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
189
0
18

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(239 citation statements)
references
References 90 publications
(125 reference statements)
11
189
0
18
Order By: Relevance
“…Estudos sugerem que a ST pode influenciar o comportamento dos indivíduos nas organizações, alterando índices de produtividade (Sánchez-Sellero et al, 2014), comprometimento organizacional (Folami, Asare, Kwesiga, & Bline, 2014) e turnover (Zopiatis, Constanti, & Theocharous, 2014). Além disso, a ST pode influenciar a esfera extralaboral, podendo favorecer ou comprometer índices de bem-estar (Bruk-Lee, Khoury, Nixon, Goh, & Spector, 2009;Satuf et al, 2016) e felicidade (Bowling, Eschleman, & Wang, 2010) Neste estudo, interessa-nos explorar e compreender a relação entre ST e bem-estar subjetivo (BES), que pode ser definido como um termo amplo utilizado para descrever o nível de bem-estar vivenciado pela pessoa, conforme a avaliação subjetiva que ela faz de sua vida.…”
unclassified
“…Estudos sugerem que a ST pode influenciar o comportamento dos indivíduos nas organizações, alterando índices de produtividade (Sánchez-Sellero et al, 2014), comprometimento organizacional (Folami, Asare, Kwesiga, & Bline, 2014) e turnover (Zopiatis, Constanti, & Theocharous, 2014). Além disso, a ST pode influenciar a esfera extralaboral, podendo favorecer ou comprometer índices de bem-estar (Bruk-Lee, Khoury, Nixon, Goh, & Spector, 2009;Satuf et al, 2016) e felicidade (Bowling, Eschleman, & Wang, 2010) Neste estudo, interessa-nos explorar e compreender a relação entre ST e bem-estar subjetivo (BES), que pode ser definido como um termo amplo utilizado para descrever o nível de bem-estar vivenciado pela pessoa, conforme a avaliação subjetiva que ela faz de sua vida.…”
unclassified
“…This commitment is regarded as a fundamental constituent of establishing and persisting long-term relationships (Cater, 2007). In a lodging context, Zopiatis, Constanti, and Theocharous (2014) empirically identified the critical role of commitment and satisfaction in reducing hotel employees' turnover intention and increasing retention rate. In their examination of hotel customers' behaviors, in her examination of hotel reward program members' behaviors, Tanford (2013) identified that the impact of commitment as well as switching costs significantly increase a function of tier level, Journal of Sustainable Tourism 1099 which eventually leads to customer retention and loyalty.…”
mentioning
confidence: 99%
“…It belongs to the responses in feelings, attitudes, or affections. Zopiatis et al (2014) proposed that work values are the goals that are relevant to the job and are the individual's internal demands and the vocational education or features that are pursued by an individual during the activities. Jamaludin (2011) proposed that work values indicate the enduring belief and standard for evaluating relevant job details, behaviors, or goals during an individual's working process.…”
Section: Work Valuesmentioning
confidence: 99%